PREVALENCE OF GASTROINTESTINAL HELMINTHS IN FREE-RANGE POULTRY (GALLUS GALLUS DOMESTICUS) IN THE NORTHEAST OF TUNISIA - Khaled Kaboudi; Nesrine Rhif; Rafika Ben Romdhane; Nadine Abdallah; Mokhtar Dhibi (Archives of Veterinary Medicine)
This study was carried out to identify and estimate the prevalence of intestinal helminths in free-range poultry (Gallus gallus domesticus), from September 2016 to December 2022. A total of 494 birds of both sexes, aged from 6 weeks to 36 weeks, were examined and necropsied. Mucosa and contents of different gastrointestinal tract segments were examined for the helminth parasites. Results showed that 38.86% (192 birds), as overall prevalence, were infected by at least one parasite species. The prevalence of gastrointestinal helminth infections was higher in young animals (under 18 weeks) (32.79%) than adults (6.07%) (p < 0.05) and during rainy and cold seasons (autumn: 59.18%; spring: 41.72%; summer: 30.7%; winter: 28.84%) (p < 0.05). Nematodes were more prevalent (30.97%) than cestodes (21.66%). The prevalence was significantly higher in young chickens compared to adult animals (p < 0.05). Among the helminths species, Raillietina genus was the most observed (22.67%) (Raillietina echinobothrida: 21.05%; Raillietina spp: 1.62%) followed by Ascaridia galli (21.25%), Heterakis gallinarum (12.35%) and Capillaria spp. (4.86%). To our knowledge, this is the first report of gastrointestinal helminths prevalence in free-range chickens in the Northeast of Tunisia. Further additional studies are needed to develop better preventive measures in free-range poultry flocks.